2022
DOI: 10.1007/s11783-022-1554-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manufactured nanomaterials on algae: Implications and applications

Abstract: The wide application of manufactured nanomaterials (MNMs) has resulted in the inevitable release of MNMs into the aquatic environment along their life cycle. As the primary producer in aquatic ecosystems, algae play a critical role in maintaining the balance of ecosystems’ energy flow, material circulation and information transmission. Thus, thoroughly understanding the biological effects of MNMs on algae as well as the underlying mechanisms is of vital importance. We conducted a comprehensive review on both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 139 publications
0
13
0
Order By: Relevance
“…13,29 Therefore, they are the main organism's that are aquatic producers of oxygen in ecosystems (through photosynthesis). 30 Algae are classified into microalgae and macroalgae. 31 It is estimated that the number of species of algae is between one and ten million, and the majority are composed of microalgae.…”
Section: Microalgae As a Raw Materials For The Green Synthesis Of Npsmentioning
confidence: 99%
“…13,29 Therefore, they are the main organism's that are aquatic producers of oxygen in ecosystems (through photosynthesis). 30 Algae are classified into microalgae and macroalgae. 31 It is estimated that the number of species of algae is between one and ten million, and the majority are composed of microalgae.…”
Section: Microalgae As a Raw Materials For The Green Synthesis Of Npsmentioning
confidence: 99%
“…The indoor dust-associated MNPs could enter and bioaccumulate in the human respiratory system (i.e., lung) , via inhalation. Because of their unique physicochemical properties (e.g., high reactivity and oxidative potential), MNPs can trigger extracellular and/or intracellular reactive oxygen species (ROS) formation, , which may damage the cell membrane and induce oxidation of cellular components (e.g., lipid peroxidation). , Long-term exposure to MNPs may cause cytotoxicity and even chronic alveolar inflammation of lung cells. , In addition, MNPs could be translocated to other organs (e.g., lymphatic system and liver) in the human body. For example, magnetic MNPs, rather than their dissolved metal compounds, can bypass the blood–brain barrier, which poses a significant threat to human health (e.g., causing neurodegenerative diseases) .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their unique physicochemical properties (e.g., high reactivity 20 and oxidative potential 21 ), MNPs can trigger extracellular and/or intracellular reactive oxygen species (ROS) formation, 14,22 which may damage the cell membrane and induce oxidation of cellular components (e.g., lipid peroxidation). 23,24 Long-term exposure to MNPs may cause cytotoxicity and even chronic alveolar inflammation of lung cells. 25,26 In addition, MNPs could be translocated to other organs (e.g., lymphatic system and liver) 27 in the human body.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This process (size reduction) increases the surface-to-volume ratio (thus surface energy), biological efficiency, and adsorption capacity of the obtained product. In addition, its chemical/physical (such as diffusion, strength, color, solubility, and quantum effects), optical, magnetic, and thermodynamic properties are significantly improved [1,2]. Innovative nanostructured materials and nanocomposites equipped with these superior properties have a wider application area (environment, agriculture, medicine, food, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Due to nanotechnological advances, NMs are estimated to be components of more than 2,000 commercial products, and this number is expected to increase significantly in the coming years. However, during the production, carrying, use, and exterminating of these products, NMs are inevitably released into the environment, especially in the waters as the final destination [2]. Keller et al [3] reported that 0.4−7% of these products eventually enter the aquatic environment, assuming that there is approximately 309,000 tons of NM production globally.…”
Section: Introductionmentioning
confidence: 99%